Islam dan Local Wisdom: Menelisik Jejak Rekonsiliasi Islam Preode Awal terhadap Ritus, Pranata Sosial dan Kultural - Qoidul Khoir; Fajar Ainol Yakin (Al Yazidiy Jurnal Sosial Humaniora dan Pendidikan, 2021)
Islam as a religion that came 14 centuries ago certainly could not escape the established civilization and culture, the plains of Arabia as the birthplace of Islam was indeed not a mainstream area of world civilization at that time, but this does not mean that Arabia is a land without capabilities and culture. It was recorded that before Islam was born, the commerce carried out by the Arabs had reached various regions outside the Arabian Peninsula, apart from that their penchant for literature made people in the Arab plains as people who had high language quality. However, many historians have created a gap between Islam and pre-Islamic Arab traditions through contrasting moral and ideological demarcations. Pre-Islamic Arab society was perceived as an ignorant society, then Islam came to liberate it. To some extent, the claim is not entirely false. However, this generalization has a negative influence in building historical criticism. This paper will focus on the dialectical relationship between local culture and Islam, especially the early Islam and the local cultural traditions of Arab society through the perspective of the Prophet's traditions. is a qualitative descriptive method by using a type of library research (Library Research) That is by reviewing books or written data that is continuous with the writing of this journal. In this case, the researcher analyzes some data that is relevant to the title being discussed. The findings in this study are that there has been reconciliation between culture and Islam since the early days of Islam, one of the evidences is the addition of the call to prayer at Friday prayers twice during the reign of Sayyidina Uthman bin Affan and this continues until now.